Discovery of small molecule FLT3 inhibitors that are able to overcome drug-resistant mutations. Issue 22 (15th November 2020) - Zhang, Guo; Zhang, Wenqing; Shen, Chenjian; Nan, Jinshan; Chen, Ming; Lai, Shusheng; Zhong, Jiemin; Li, Bolin; Wang, Tianqi; Wang, Yifei; Yang, Shengyong; Li, Linli
Graphical abstract: Abstract: Herein we report the discovery of 1-(5-(tert-butyl)isoxazol-3-yl)-3- (3-fluorophenyl)urea derivatives as new FLT3 inhibitors that are able to overcome the drug resistance mutations: the secondary D835Y and F691L mutations on the basis of the internal tandem duplications (ITD) mutation of FLT3 (FLT3-ITD/D835Y and FLT3-ITD/F691L, respectively). The most potent compound corresponds to 1-(5-(tert-butyl)isoxazol-3-yl)-3-(4-((6, 7-dimethoxyquinolin-4-yl)oxy)-3- fluorophenyl)urea (4d ), which showed IC50 s (half maximal inhibitory concentrations) of 0.072 nM, 5.86 nM and 3.48 nM against FLT3-ITD, FLT3-ITD/F691L and FLT3-ITD/D835Y, respectively. Compound 4d also showed good selectivity for FLT3 in a kinase profiling assay. Collectively, 4d could be a good lead compound and deserves further in-depth studies.